Outcomes of pediatric glioblastoma treated with adjuvant chemoradiation with temozolomide and correlation with prognostic factors - Supriya Mallick; Ajeet Kumar Gandhi; Nikhil P Joshi; Anupam Kumar; Tarun Puri; Daya Nand Sharma; Kunhi Parambath Haresh; Subhash Gupta; Pramod Kumar Julka; Goura Kisor Rath; Chitra Sarkar (Indian Journal of Medical and Paediatric Oncology)
Background: Pediatric glioblastoma (pGBM) patients are underrepresented in major trials for this disease. We aimed to explore the outcome of pGBM patients treated with concurrent and adjuvant temozolomide (TMZ). Materials and Methods: 23 patients of pGBM treated from 2004 to 2010 were included in this retrospective analysis. Adjuvant therapy included conformal radiation 60 gray at 2 gray/fraction daily over 6 weeks with concurrent TMZ 75 mg/m 2 followed by six cycles of adjuvant TMZ 150-200 mg/m 2 (day 1-5) every 4 weeks. Kaplan-Meier estimates of overall survival (OS) were determined. Univariate analysis with log-rank test was used to determine the impact of prognostic variables on survival. Results: Median age at presentation was 11.5 years (range: 7-19 years) and M:F ratio was 15:8. All patients underwent maximal safe surgical resection; 13 gross total resection and 10 sub-total resection. At a median follow-up of 18 months (range: 2.1-126 months), the estimated median OS was 41.9 months. The estimated median OS for patients receiving only concurrent TMZ was 8 months while that for patients receiving concurrent and adjuvant TMZ was 41.9 months (P = 0.081). Estimated median OS for patients who did not complete six cycles of adjuvant TMZ was 9.5 months versus not reached for those who completed at least six cycles (P = 0.0005). Other prognostic factors did not correlate with survival. Conclusions: Our study shows the benefit of TMZ for pGBM patients. Both concurrent and adjuvant TMZ seem to be important for superior OS in this group of patients.